×

#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
Prove that (1-w)(1-w^2)(1-w^4)(1-w^8)=9 in algebra method.
Prove that (1-w)(1-w^2)(1-w^4)(1-w^8)=9 in algebra method.

```
3 years ago

## Answers : (4)

Arun
25768 Points
```							 We have 1 + w + w2 = 0 & w3 = 1(1 – w)(1 – w2)(1 – w4)(1 – w5) = (1 – w)(1 – w2)(1 – w3.w)(1 – w3.w2)= (1 – w)(1 – w2)(1 – w)(1 – w2)  (Since w3 = 1)= (1 – w)2(1 – w2)2=(1 – 2w + w2)(1 – 2w2 + w4) = (1 – 2w + w2) (1 – 2w2 – w3.w) = (1 – 2w + w2) (1 – 2w2 – w) = ( – w – 2w)( – w2 – 2w2)  (since 1 + w + w2 = 0)= ( – 3w) ( – 3w2) = 9w3 = 9
```
3 years ago
Rishi Sharma
629 Points
```							Dear Student,Please find below the solution to your problem.We have 1 + w + w2= 0 & w3= 1(1 – w)(1 – w2)(1 – w4)(1 – w5) = (1 – w)(1 – w2)(1 – w3.w)(1 – w3.w2)= (1 – w)(1 – w2)(1 – w)(1 – w2) (Since w3= 1)= (1 – w)2(1 – w2)2=(1 – 2w + w2)(1 – 2w2+ w4) = (1 – 2w + w2) (1 – 2w2– w3.w) =(1 – 2w + w2) (1 – 2w2– w)= ( – w – 2w)( – w2– 2w2) (since1 + w + w2= 0)= ( – 3w) ( – 3w2) = 9w3= 9Thanks and Regards
```
5 months ago
Shanmukha Rao
27 Points
```							We have 1 + w + w^2= 0 & w^3= 1=(1 – w)(1 – w^2)(1 – w^4)(1 – w^5) = (1 – w)(1 – w^2)(1 – w^3.w)(1 – w^3.w^2)= (1 – w)(1 – w^2)(1 – w)(1 – w^2)                         (Since w^3= 1)= (1 – w)^2(1 – w^2)^2=(1 – 2w + w2)(1 – 2w2+ w4) = (1 – 2w + w^2) (1 – 2w^2– w^3.w) =(1 – 2w + w^2) (1 – 2w^2– w)= ( – w – 2w)( – w^2– 2w^2)                 (since1 + w + w^2= 0)= ( – 3w) ( – 3w^2) = 9w^3= 9
```
one month ago
Shanmukha Rao
27 Points
```							We have: 1 + w + w^2= 0 & w^3= 1=(1 – w)(1 – w^2)(1 – w^4)(1 – w^5) = (1 – w)(1 – w^2)(1 – w^3.w)(1 – w^3.w^2)= (1 – w)(1 – w^2)(1 – w)(1 – w^2)                         (Since w^3= 1)= (1 – w)^2(1 – w^2)^2=(1 – 2w + w2)(1 – 2w2+ w4) = (1 – 2w + w^2) (1 – 2w^2– w^3.w) =(1 – 2w + w^2) (1 – 2w^2– w)= ( – w – 2w)( – w^2– 2w^2)                 (since1 + w + w^2= 0)= ( – 3w) ( – 3w^2) = 9w^3= 9
```
one month ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies

## Other Related Questions on Algebra

View all Questions »

### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution

### Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions